P124 Bullying and Health Care Utilisation in 9-year-olds: Baseline Analysis of a Longitudinal Cohort. (13th September 2016) - Hayes, CB; Reulbach, U; Kelly, D; Taut, C; Nixon, E; Zgaga, L; Williams, J; O'Dowd, T
Abstract : Background: Being victimised by bullying is strongly associated with having an underlying chronic condition. The aim of this study was to determine whether primary and/or secondary healthcare utilisation (HCU) is increased in children who are bullied independent of having an underlying chronic illness or disability. Methods: Cross-sectional survey of the first wave of the childhood (9-year-old) cohort of the Irish National Longitudinal Study of Children, encompassing 8, 568 9-year-olds and their primary carers. Bully victimisation was assessed by a self-reported questionnaire completed by the child at home. The principal HCU outcomes obtained by interview-administered questionnaire with the primary caregiver at home were: visits to general practitioner (GP), Mental Health Practitioner (MHP) and nights spent in hospital in the previous 12 months. Results: In logistic regression models, being victimised by bullying independently increased GP visits (OR = 1.13, 95% CI: 1.03–1.25, p = 0.02); MHP visits (OR = 1.31, 95% CI: 1.05–1.63, p = 0.02), though not nights in hospital (OR = 1.07 95% CI: 0.97–1.18, p = 0.18), irrespective of presence of chronic illness or disability. Gender stratified Poisson models demonstrated that victimised girls made increased GP visits (RR = 1.14, 95% CI: 1.06–1.23, p < 0.001) and spent nights in hospital (RR = 1.10, 95% CI: 1.04–1.15, p < 0.001); whereas victimised boys were more likely to contact MHPs (OR = 1.21, 95% CI: 1.02–1.44, p = 0.03). Conclusion: 9-year-olds who are victims of bullying are more likely to utilise healthcare services. Different types of HCU patterns were observed by gender. Our study suggests health professionals need to be vigilant that medically unexplained symptoms and behavioural problems in children may be manifestations of bully victimisation, which may present differently in boys and girls. This has important implications for early detection of bullying and appropriate management of victimised children.